Using U‐Pace instruction to improve the academic performance of economically disadvantaged undergraduates. (14th March 2016) - Fleming, R.; Stoiber, L.C.; Pfeiffer, H.M.; Kienzler, S.E.; Fleming, R.R.; Pedrick, L.E.; Barth, D.J.; Reddy, D.M.
Abstract: This study was undertaken to evaluate whether the student success associated with the U‐Pace instructional approach, which integrates mastery‐based learning with proactive instructor support in an online learning environment, would replicate for both economically disadvantaged students and students who are not economically disadvantaged. Undergraduates were enrolled in U‐Pace (intervention) or comparison sections of a gateway course at two universities with different learning management systems. Course content was held constant. At both universities, intervention students earned a significantly greater percentage of objectively determined final grades of A or B. This academic success was found for both economically disadvantaged intervention students and intervention students who were not economically disadvantaged. Improvement from the beginning to the end of the semester in intervention students' rate of mastering concepts was found at University 1, but not at University 2. The assessment of learning conducted at University 1, independent of final course grades, showed that intervention students scored significantly higher on the proctored cumulative exam than comparison students. Findings suggest that the U‐Pace instructional intervention holds promise for increasing the success of undergraduates regardless of economic status.